Offshore Technology Conference 1976
DOI: 10.4043/2453-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Dispersal Patterns as Clues to Placer Like Platinum Accumulation in and near Chagvan Bay, Alaska

Abstract: The modern sediments of Chagvan Bay, Alaska contain zones of platinum enrichment which suggest an external source of platinum-host sediments. Two mathematical sediment tracing techniques, based on vector and multiple regression analyses of geochemical data, are used to determine the provenance and dispersal patterns of the bay deposits. Criteria for the selection of natural sediment tracers are presented, and the application of tracing techniques to the exploration for high latitude marine placers is discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The mining history and general and economic geology of this region have been extensively reported by Mertie (1940;1969;. Small zones of platinum enrichment (0.03--0.5 ppm) above baseline levels (<0.01 ppm) also occur in the modern sediments of Chagvan Bay (Owen and Moore, 1976) and in the nearshore surflcial sediments of the Bering Sea adjacent to the bay (Moore and Welkie, 1976). The spatial extent and value of platinum in these modern deposits has yet to be determined.…”
Section: Al'?a Tmentioning
confidence: 81%
See 3 more Smart Citations
“…The mining history and general and economic geology of this region have been extensively reported by Mertie (1940;1969;. Small zones of platinum enrichment (0.03--0.5 ppm) above baseline levels (<0.01 ppm) also occur in the modern sediments of Chagvan Bay (Owen and Moore, 1976) and in the nearshore surflcial sediments of the Bering Sea adjacent to the bay (Moore and Welkie, 1976). The spatial extent and value of platinum in these modern deposits has yet to be determined.…”
Section: Al'?a Tmentioning
confidence: 81%
“…Lithic fragments are predominant in the principal gravel mode (--3 to --2 4) and quartz and feldspar grains are predominant in the fine sand mode (2--3 4). Comparison studies of the trace-element geochemistry of the principal gravel and fine sand modes with detrital material from apparent source areas around Chagvan Bay have shown that these two modes are derived from the coastal bluffs and Bering Sea shelf, respectively (Owen, 1975;Owen and Moore, 1976). Identifiable grains in the coarse silt mode (4--5 4) from the Kinegnak River are composed primarily of quartz.…”
Section: Textural and Mineralogical Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations